In silico analysis of crustacean hyperglycemic hormone family G protein-coupled receptor candidates - Kozma, Mihika T.; Pérez-Moreno, Jorge L.; Gandhi, Neha S.; Hernandez Jeppesen, Luisanna; Durica, David S.; Ventura, Tomer; Mykles, Donald L. (Frontiers in Endocrinology, 2024)
Ecdysteroid molting hormone synthesis is directed by a pair of molting glands or Y-organs (YOs), and this synthesis is inhibited by molt inhibiting hormone (MIH). MIH is a member of the crustacean hyperglycemic hormone (CHH) neuropeptide superfamily, which includes CHH and insect ion transport peptide (ITP). It is hypothesized that the MIH receptor is a Class A (Rhodopsin-like) G protein-coupled receptor (GPCR). The YO of the blackback land crab, Gecarcinus lateralis, expresses 49 Class A GPCRs, three of which (Gl-CHHR-A9, -A10, and -A12) were provisionally assigned as CHH-like receptors. CrusTome, a transcriptome database assembled from 189 crustaceans and 12 ecdysozoan outgroups, was used to deorphanize candidate MIH/CHH GPCRs, relying on sequence homology to three functionally characterized ITP receptors (BNGR-A2, BNGR-A24, and BNGR-A34) in the silk moth, Bombyx mori. Phylogenetic analysis and multiple sequence alignments across major taxonomic groups revealed extensive expansion and diversification of crustacean A2, A24, and A34 receptors, designated CHH Family Receptor Candidates (CFRCs). The A2 clade was divided into three subclades; A24 clade was divided into five subclades; and A34 was divided into six subclades. The subclades were distinguished by conserved motifs in extracellular loop (ECL) 2 and ECL3 in the ligand-binding region. Eleven of the 14 subclades occurred in decapod crustaceans. In G. lateralis, seven CFRC sequences, designated Gl-CFRC-A2a1, -A24a, -A24b1, -A24b2, -A34a2, -A34b1, and -A34b2, were identified; the three A34 sequences corresponded to Gl-GPCR-A12, -A9, and A10, respectively. ECL2 in all the CFRC sequences had a two-stranded beta-sheet structure similar to human Class A GPCRs, whereas the ECL2 of decapod CFRC-A34b1/b2 had an additional two-stranded beta-sheet. We hypothesize that this second beta-sheet on ECL2 plays a role in MIH/CHH binding and activation, which will be investigated further with functional assays.